2013
DOI: 10.2478/bpasts-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of active destructive processes as a diagnostic tool for the structure technical state evaluation

Abstract: Abstract. In this paper, a global monitoring system based on the measurement of acoustic emission (AE) due to active deterioration processes is presented. This allows us to examine the entire volume of an element and to locate and identify the type and the dynamics of the deterioration processes under service conditions. The resulting data are used to determine and locate the damage processes that are dangerous in construction made of pre-stress concrete, steel and fiber glass and to assess the general conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…During the study engineers found that cracks are "normal" and accepted ranges of code, mainly there are cracks caused by concrete shrinkage [6,7]. But advocated monitor and regularly check the development of cracks in places prone, especially in connecting elements between the steel girder and concrete, in the middle of the spans, in concrete arch to be possible to prevent unexpected symptom [7,8].…”
Section: Assessment Of Structure Statementioning
confidence: 99%
“…During the study engineers found that cracks are "normal" and accepted ranges of code, mainly there are cracks caused by concrete shrinkage [6,7]. But advocated monitor and regularly check the development of cracks in places prone, especially in connecting elements between the steel girder and concrete, in the middle of the spans, in concrete arch to be possible to prevent unexpected symptom [7,8].…”
Section: Assessment Of Structure Statementioning
confidence: 99%
“…Therefore, elaboration of the reliable nondestructive method for an adhesion mapping could provide a quite advantageous alternative. Recently, a growing interest has been noted in the application of nondestructive techniques (NDT) for evaluation of concrete structures [6][7][8]. A majority of NDT methods mentioned in EN 1504-10 and ACI Concrete Repair Manual for assessment of concrete structures are based on propagation of stress waves.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth highlighting that so far, the majority of research on fibrecement materials has been limited to determining standard physical and mechanical parameters [5,6]. It is also possible to see the results of research conducted with the use of non-destructive methods, which as a diagnostic method is widely used and simultaneously developed worldwide with reference to steel and concrete constructions as well as composite materials [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%